Limites da justiça de transição à brasileira: uma análise do Caso Herzog - Vasconcelos Filho, Antonio Alves de (2022)
A period of authoritarian rule leaves wounds that do not heal for a long time, requiring a series of measures aimed at strengthening the newly established democracy and protecting human rights. The present dissertation aims to analyze the Brazilian transition, from the Herzog Case, considering the decision of the Inter-American Court that condemned and held the Brazilian State accountable, taking into account the moment of opening, in the controlled exit of the Dictatorship and the granting of Amnesty under the terms of the regime. In this sense, the problem is present in the investigation of how Amnesty affects the lack of accountability of dictatorship agents and the incomplete consolidation of Brazilian democracy. Therefore, a Case Study of the Brazilian transition is aimed at, taking the Herzog Case as a central reference, but not without first deepening the historical and political context of the period that marks the end of the authoritarian regime. Through the following research, the objective is to understand the concept of transitional justice and the Brazilian experience, to analyze the opening period, the moment of Herzog's death and in what terms the Brazilian amnesty happened, to observe from the Herzog Case and of the Inter-American Court's decision, how the national institutions received this decision and its meaning for the Brazilian transitional justice. Therefore, the work that follows used a qualitative approach in a Case Study, through a research with a review of the bibliography on the subject and using official documents, such as the Herzog dossier present in the national archive, the judgments on the Herzog Case, furthermore, interdisciplinary bases were sought to carry out the analyzes with a main focus on political science, history and law.